The original Torah: the political intent of the Bible's writers - Sperling, S. David (Reappraisals in Jewish social and intellectual history, 1998)
It says in the Torah -- History and allegory -- The allegory of servitude in Egypt and the Exodus -- Yahweh's berît (covenant) : which came first--sex or politics? -- Abraham -- Jacob, Jeroboam, and Joseph -- Aaron -- Moses.